2005
DOI: 10.1007/s00586-005-1020-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lumbar sympathectomy on pain behavioral changes caused by nucleus pulposus-induced spinal nerve damage in rats

Abstract: IntroductionIt has been reported that nucleus pulposus in the epidural space induces spinal nerve root damage, not only by mechanical but also by chemical mechanisms as nucleus pulposus is capable of producing proinflammatory cytokines [5,14,16,17,19,21,23,29]. There have been a number of recent reports regarding the pain behavior due to lumbar disk herniation in rats [7,18,20,24]. One well-characterized model involves L4/5 disk incision and/or displacement of the adjacent spinal nerve in rats. These studies i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
2
8
0
Order By: Relevance
“…It has also been reported that unilateral sympathectomy 1 day before spinal nerve damage prevents pain behavior changes. 11 In the present study, our results suggest that unilateral sympathectomy just before nerve injury can prevent the development of mechanical allodynia. The threshold showed high variability in the sympathectomy and sham groups compared with the crush group.…”
Section: Discussionsupporting
confidence: 60%
“…It has also been reported that unilateral sympathectomy 1 day before spinal nerve damage prevents pain behavior changes. 11 In the present study, our results suggest that unilateral sympathectomy just before nerve injury can prevent the development of mechanical allodynia. The threshold showed high variability in the sympathectomy and sham groups compared with the crush group.…”
Section: Discussionsupporting
confidence: 60%
“…Meanwhile, several studies have also reported that sympathectomy reduces mechanical allodynia and thermal hyperalgesia in various animal pain models. 2,8,17 Clinical reports have shown that a sympathetic nerve block reduces lumbar radicular pain 28,29 and sympathectomy increases intraradicular, 30 cauda equina, 31 and sciatic nerve blood flow. 32 It has also been suggested that the recovery of reduced DRG blood flow might prevent allodynia in a radicular pain model.…”
Section: Discussionmentioning
confidence: 99%
“…32 It has also been suggested that the recovery of reduced DRG blood flow might prevent allodynia in a radicular pain model. 8 Sekiguchi et al 2 reported that sympathectomy reduced mechanical allodynia, tumor necrosis factor-alpha (TNF-α) expression, and DRG neuron apoptosis following nerve root crush injury. 2 Chen et al 17 showed that surgical and chemical sympathectomy significantly attenuated bee venom-induced mechanical hyperalgesia and inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mizuno et al reported sympathetic nerve fibers increased in corresponding DRG neurons in the root constriction model [30]. Sympathectomy alleviates pain behaviors such as mechanical allodynia and thermal hyperalgesia in animal models [20,24,30,31,37]. In clinical cases, lumbar sympathetic block has been performed to relieve chronic pain, including intractable lumbar radicular pain [6,32,46].…”
Section: Introductionmentioning
confidence: 99%